Dictionary of social work - Pierson, John , 1944-; Thomas, Martin , 1943- (Maidenhead, Berkshire, England ; New York : Open University Press, 2010)
This is a one-stop-shop for students looking to get an insight into the key issues and concepts involved in social work. This dictionary offers both undergraduate and postgraduate students a resource that they will be able to refer to again and again during their studies
Includes bibliographical references
Keywords: Social service -- Dictionaries